The function of narrative in the Saffarzadeh's poetry based on the narratology of Barthes's theory" - Ali Ali Ziaaddini Dashtkhaki; Sayyed Javad Mortezayi (Literary Arts, 2016)
Abstract Authenticating to reality and merging in identity have effect on progress continuation on new poesy in Iran with all its physical and internal characteristics. Modern poet has found that he can assemble in consistent components in a meaningful totality and it makes possible for sporadic ingredients to become systematic and convert the appraisal moment to ontological moment. Narrating in poetry is the outcome of this process. In fact, narrative science is a kind of formalist – structural criticism which studies the dominant relations in the structure of a literary work. Narration is the time expression, the song of life, the experience of mind, the existence language and the events meaning. Narrative is the reflection of ideas which have been lived and its basis is this notion that every event is followed by another event. Therefore narration is the result of the sequence of events. This study provides the necessary background for arriving to narrative function by presenting the narration science and studding the relation between the structuralism and narrative science. The function that always through the narrative communication and using the characters speech has been followed in a unite body which called narrative. In narrative poem the function unlike the themes are not the elements inside the narration but themselves are narration, and the narration is not anything but the sequence of narration function. In this research, the function of narration in Iran contemporary poetry is studies according to Barth and in three categories of determination unities and functional grammar. The study sample is the poems of Tahere Saffarzadeh, which is one of the contemporary Iranian poets. The narrative functions in this poet poems are been analyzed according to librarian method, content analysis and comparison. The basic concept of theory, the study diagram of functions which pivotal role, the main functions which are out spread in narrative text, all of them are the catalyst of narrative. The indexes and informative functional grammar are the other major center in studying of narrative functions of Saffarzadeh In another part of this research the Saffarzadeh poetic life in three different periods are studied. The Moonlight passerby and Second book collections are the poet’s outcome in this period. The first period of Saffarzadeh poetic in term of the narrative poems, in comparison of the next period is less worth. The narrative functions of these poems are surveyed in this article. The second period of Saffarzadeh poetic life is (1347- 1356) which is her narrative culmination in poetry. Three poetic collector, the dam and arms, the ring in delta and the fifth travel are her activity outcome in this period. The period in which according to statistics Saffarzadeh has chosen the narrative approach for reaching to personal style. In this period the narrative functions of Saffarzadeh poem have a widespread area. The readings of her poem express this point that her poetic has found trend from simplicity to complexity and from descriptive models to narrative models. She has tries to make a bridge between thought and narration according to narration and relying in this reality that narration is dynamic can achieve to her goal which is making movement in the mind of audience. The Saffarzadeh poetic narrative which is inspired from Iran political and social information in Pahlavi period, often have messages which invite the audience to morality, commitment, human and religious values and propose thoroughly in the form of promising literature since 1368.